Taller trabajamos con porcelana en frio para mejorar la motricidad fina en los niños de 3 años de la I.E Nº215 – 2018 - Castillo Amao, Diana Gabriela (2019)
The present research entitled Workshop we work with cold porcelain to improve fine engineering in children of 3 years of the I.E No. 215 - 2018, aims to address the problem presented by most students in the preschool age in their fine motor skills. Through manual work in cold porcelain, which will establish in children an adequate development of fine motor skills that will benefit the integral development of the child._x000D_ The research was applied with pre - experimental design, with a single experimental group, with pre test and post test._x000D_ This research was carried out with a sample of 29 children of the light blue_x000D_ classroom consisting of 14 men and 15 women of the I.E. Nº215._x000D_ The results obtained in the pre test showed that 86.2% of students were at the por level and 13.8% at a sufficient level with respect to fine motor skills; but after having applied the Workshop "We work cold porcelain"; 82.8% obtained a sufficient level and only 17.2% at a deficient level. It is denoted that there was a significant difference in the improvement of fine motor skills of the experimental group in the improvement of the four dimensions: visomanual coordination, gestural coordination, phonetic coordination and facial coordination